2019
DOI: 10.1177/0300060519863497
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between malnutrition and health-related quality of life (HRQOL) in elderly Iranian adults

Abstract: Objectives: We aimed to evaluate the association of nutritional status and health-related quality of life (HRQOL) among elderly Iranian residents. Methods: We used the 36-item Short Form Health Survey (SF-36) to assess HRQOL among participants with normal nutrition status, at risk of malnutrition, and malnourished. Results: Mean group scores for the Physical Component Summary (PCS) of the SF-36 were 44, 36.5, and 29.0 for normal, at-risk, and malnourished groups, respectively; for the Mental Component Summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
3
15
0
7
Order By: Relevance
“…Coexisting diseases and their related indexes such as the CCI and the use of multiple medications (polypharmacy) might be used as the indicators for this purpose (3,7). Polypharmacy may have a negative impact on nutritional status due to drug-food interactions or gastrointestinal complaints (3,7). Our results were consistent with these studies.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Coexisting diseases and their related indexes such as the CCI and the use of multiple medications (polypharmacy) might be used as the indicators for this purpose (3,7). Polypharmacy may have a negative impact on nutritional status due to drug-food interactions or gastrointestinal complaints (3,7). Our results were consistent with these studies.…”
Section: Discussionsupporting
confidence: 89%
“…Depending on the study groups' characteristics and the country of the study, reported prevalence of nutritional risk and malnutrition shows significant variation. The combined rates of nutritional risk and malnutrition (based on the MNA scores) range from 14.3% to 82.6% (1,4,5,7,(19)(20)(21)(22). Several factors have been speculated to explain these variations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations